Implementation of Guidance-Based Educational Supervision in Improving Teachers’ Pedagogical Abilities - Hasinah, Hasinah (PPSDP International Journal of Education, 2024)
The purpose of this study is to explain how internal supervision can be used to raise student standards. The study was conducted in Palembang’s SMA Yulis Palembang. The principal of the school and five of the class XI teachers are the sources of the research data. Qualitative methodologies are employed in the research. Interviews, documentation, and observational methods were used in the data collection process. Qualitative methods were applied to the analysis of the data. The study’s findings demonstrate that guidance-based educational supervision activities are implemented in four interconnected stages to enhance teachers’ pedagogical skills at SMA Yulis Palembang. These stages include indirect class visits, teacher teaching and learning documentation, and in-person interactions to validate findings pertaining to teaching and learning activities. The findings of this study offer school’s principals a helpful substitute: guidance-based educational supervision that is conducted on a regular basis to support teachers’ professional development. Six characteristics make up the profile of strengthening Pancasila itself: self-assurance and dedication to the all-powerful God, the world’s diverse traits, teamwork, autonomy, fundamental reasoning, and creative thought. Usually, drained configuration Understudies might compete inside the educational system to gain the resources necessary to become members of a society that is genuinely better.